Effect of duration of dystocia on haematobiochemical alterations in buff aloes - DHINDSA, S S; GANDOTRA, V K; NANDA, A S; SINGH, S P S; JINDAL, R; BRAR, P S (The Indian Journal of Animal Reproduction, 2023)
Dystocia leads to death of the dam and the calf especially in delayed cases. The present study was undertaken to assess certain haematobiochemical alterations in thirty three dystocia affected buffaloes, divided into four groups with labour pains less than 12 hours (group A; n=07), 12-24 hours (group B; 11=12), 24-36 hours (group_C; n=06) or more than 36 hours (group D; n=08). Haemoglobin (8.6-9.93 g/dl) and packed cell volume (30-36%) remained within the normal physiological range in different groups. Glucose, insulin, blood urea nitrogen and creatinine concentrations increased significantly from initial values of 98.77 mg/di, 8.25 mU/ml, 10.51 mg/di and 2.21 mg/di , respectively, in group A to 180.22 mg/di, 61.03 mU/ml, 20.51 mg/di and 3.96 mg/di, respectively, in group D. Total plasma protein (5.72 g/dl) and plasma (4.36%) and blood (6.42%) volumes were significantly lower in group D as compared to other groups. It is concluded that increased concentrations of blood urea nitrogen and creatinine and decreased circulatory volumes over the passage of time in buffaloes following dystocia indicated the progression of dehydration and toxaemia in protracted cases.